Ta`līm al-Ḥiwār Bi at-Tamṡīl Li Tarqiyyah Qudrah aṭ-Ṭalabah `Alā at-Takallum Bi al-Lughah al-`Arabiyyah (Dirāsah Tajrībiyyah Bi Ma`had Bāb an-Najāḥ al-`Aṣrī Banda Aceh): (تعليم الحوار بالتمثيل لترقية قدرة الطلبة على التكلم باللغة العربية (دراسة تجريبية بمعهد باب النجاح العصري بندا أتشيه - Zikrullah Nuzuli; Azman Ismail (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The method of dialog (conversational Method) is one method of teaching foreign languages ​​such as Arabic, English, or other languages ​​by directly inviting students to dialogue/speak with the foreign language being taught. Playing drama is one way to make it easier for students to remember Arabic vocab. The conversational method intended here is a way of teaching by dramatizing behavior in the form of social relations. As for the problems that researchers encounter at the modern Babun Najah boarding school, some students at the Modern Pesantren Babun Najah are less able to understand the language when dialoguing with Arabic with their friends well and it is also difficult to pronounce the Arabic language. From these problems, the researcher wants to discuss research entitled